Pegylated Interferon Alpha-2b Related Delirium - Ustun, Cemal; Ustun, Suzan; Demir, Caner Feyzi (Duzce Univ, 2012)
The adverse effects of Pegylated interferon used in the treatment of chronic viral hepatitis are quite frequent. Pegylated interferon alpha-2b was started to a 44-years old male patient with chronic hepatitis B at the dose of 1.5 mcg/kg/week subcutaneously. After the first dose of the treatment; incoherent speaking, confusion, sensation, and orientation disorder occurred in the patient. The delirium was understood to develop in the patient due to pegylated interferon alpha-2b after consultation of the neurology clinic. Haloperidol 2.5 mg three times daily was started for the treatment of delirium. After the first dose of haloperidol, the delirium condition was recovered. Severe neuropsychiatric adverse effects may occur due to interferon treatment. Thus, the first dose of interferon treatment should be given to patients by monitoring in hospital.
Keywords: Hepatitis; Viral; Interferon Alpha; Side effects; Delirium